2013
DOI: 10.1016/j.radmeas.2013.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy out-of-field dosimetry: Experimental and computational results for photons in a water tank

Abstract: et al.. Radiotherapy out-of-field dosimetry: Experimental and computational results for photons in a water tank. Radiation Measurements, Elsevier, 2013, 57, pp.Radiotherapy out-of-field dosimetry: Experimental and computational results for photons in a water tank, Radiation Measurements (2013), Highlights: Dosimeters based on OSL, TLD and RPL have been compared for radiotherapy purposes.  Irradiations have been performed in a water phantom located in and out of the beam.  Doses have been studied for three r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 8 publications
1
23
0
3
Order By: Relevance
“…As these spectrum variations are unknown, it is difficult to properly evaluate the out-of-field dose uncertainty. A work from Bordy et al [91] estimated the uncertainty for out-of-field measurements by optically stimulated luminescence detectors (OSL) by looking at all the sources of uncertainty and combining them in a model following the guide to the expression of uncertainty in measurement (GUM). They estimated a maximum uncertainty of 4.5% (1 sigma).…”
Section: Estimation Of the Dose At The Point Or Volume Of Interestmentioning
confidence: 99%
“…As these spectrum variations are unknown, it is difficult to properly evaluate the out-of-field dose uncertainty. A work from Bordy et al [91] estimated the uncertainty for out-of-field measurements by optically stimulated luminescence detectors (OSL) by looking at all the sources of uncertainty and combining them in a model following the guide to the expression of uncertainty in measurement (GUM). They estimated a maximum uncertainty of 4.5% (1 sigma).…”
Section: Estimation Of the Dose At The Point Or Volume Of Interestmentioning
confidence: 99%
“…1 These experiments were specifically designed to yield dosimetric data that was needed to understand and model the physics of stray radiation exposure. The measurement methods and a limited number of preliminary results were previously reported by Bordy et al 28 The EURADOS dataset consists of measurements made with multiple types thermoluminescent dosimeters (TLDs), radiophotoluminescent dosimeters (RPLs), and optically stimulated luminescent dosimeters (OSLDs) of doses delivered by a Saturne 43 linac (GE Medical Systems, USA). The calibration procedure for the various types of dosimeters is described by Kne zevi c et al 29 Doses were measured at various locations inside a 30 9 30 9 60 cm 3 water phantom.…”
Section: B Measurementsmentioning
confidence: 99%
“…With the obtained results, the irradiated mass was estimated and a better agreement on RE of 0.7%-8% was observed despite of the uncertainties 11 . It was concluded that the absorbed dose delivered by low photon energy is not accurately known 11 On the other hand, outside of radiotherapy fields where low photon energy spectra exist 16,17 discrepancies are commonly observed on the absorbed dose measured with different dosimeters [18][19][20] . This can be associated to two possible phenomena: a lack of information about the electron interaction at low energy and/or the limited understanding about the relationship between the absorbed dose and the dosimeter's response.…”
mentioning
confidence: 99%